Performance Analysis of AODV Based Maximum Energy Level Routing in Ad-Hoc Networks - Gurlhosur, Punam Karadge; Sankpal, Dr. S.V. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Advances in wireless communications have enabled the development of networks of a large number of small inexpensive, low-power multifunctional devices. These wireless Adhoc networks present a very interesting and challenging area and have tremendous potential applications. Communication protocols are the heart and soul of any communication network and the same is true for the Adhoc networks. Because of their great potential for providing safer and healthier environments for human beings they have attracted extensive interest from industry and academia. These Adhoc networks are usually operated in energy constraint environments. Therefore, from a networking perspective, energy efficiency is a critical objective in the design of communication protocols.This paper describes improvement of an energy efficiency routing for ad hoc network utilizing the high energy paths. We present a comparative analysis of existing AODV protocol and energy efficient AODV protocol which is modified to improve network lifetime in MANET. Simulation results indicate that the routing schemes are more efficient than existing well-known routing protocol.